Shattering Warmth: The Psychological Impact of Domestic Violence on Female Children - Zahra, Cut Fatimah; Ramadhani, Nurul; Umaina, Rauzatul; Waddah, Syifa Rahimatul; Indah, Sri; Rahmasari, Ulfa; Suzanna, Ella (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
This study aims to reveal the impact of domestic violence on the psychological dynamics of girls who have experienced violence since childhood. Domestic violence often leaves deep emotional scars, especially for children who become hidden victims of family conflicts. This research employs a qualitative approach using a case study method to gain an in-depth understanding of the experiences of the subject, identified as K, an adult woman who endured physical, verbal, and economic violence, as well as sexual abuse by her stepfather. The findings indicate that such violence leads to anxiety, low self-esteem, difficulties in social relationships, and challenges in forming healthy relationships. The subject also exhibits ineffective coping mechanisms in dealing with trauma, such as crying and channeling emotions through online gaming. The lack of support and protection from her mother has resulted in attachment disturbances in the mother-child relationship. This study concludes that psychological interventions through forgiveness therapy and art therapy are necessary to help alleviate anxiety and trauma, while strong social support is crucial for improving the subjects self-esteem and social relationships. The implications of this research highlight the need for increased awareness and social support for domestic violence victims to prevent long-term adverse effects.